2018
DOI: 10.1177/1534735418774410
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Study on the Antitumor Effect and Mechanism of Triphala Against Gynecological Cancers Based on Network Pharmacological Prediction and In Vitro Experimental Validation

Abstract: Objectives. Triphala is a herbal medicine that has been widely used for treating a variety of ailments. This study aims to systematically analyze the antitumor effects of Triphala on gynecological cancers. Methods. The antineoplastic activities of Triphala on gynecological cancers were analyzed using network pharmacology-based strategies. Afterward, the human ovarian cancer cell line SK-OV-3, cervical cancer cell line HeLa, and endometrial cancer cell line HEC-1-B were selected for experimetal valification. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The antiproliferative and proapoptotic activities were confirmed by cell cycle analysis and expression of Ki-67 protein. It was also found that Triphala decreased the expression of phospho-Akt, phospho-p44/42, and phospho-NF-κB p56 in these gynecological cancer cells, which indicated that MAPK/ERK, PI3K/Akt/mTOR, and NF-κB/p53 signaling pathways were the possible mechanism of Triphala-induced apoptosis [60]. Besides its anti-proliferative and apoptotic effects, Triphala suppressed cell migration of cancer cells in vitro thus indicating its anti-metastatic potential [58].…”
Section: In Vitro Studiesmentioning
confidence: 79%
See 2 more Smart Citations
“…The antiproliferative and proapoptotic activities were confirmed by cell cycle analysis and expression of Ki-67 protein. It was also found that Triphala decreased the expression of phospho-Akt, phospho-p44/42, and phospho-NF-κB p56 in these gynecological cancer cells, which indicated that MAPK/ERK, PI3K/Akt/mTOR, and NF-κB/p53 signaling pathways were the possible mechanism of Triphala-induced apoptosis [60]. Besides its anti-proliferative and apoptotic effects, Triphala suppressed cell migration of cancer cells in vitro thus indicating its anti-metastatic potential [58].…”
Section: In Vitro Studiesmentioning
confidence: 79%
“…[59] Inhibits proliferation of gynecological cancers cell with IC50 values of 98.28-101.23 µg/mL against SKOV-3, HeLa, and HEC-1B cells. [60] Inhibits proliferation of HeLa, PANC-1, and MDA-MB-231 cells and suppresses the clonogenicity of HeLa cells. [61] Inhibits proliferation of HCT116 and HCCSCs cells independent of p53 status.…”
Section: Therapeuticmentioning
confidence: 99%
See 1 more Smart Citation
“…(TC), also known as the 'Triphala'. The proportion of 1:1:1 or even 1:1:2, each of which consists of a variety of structurally varied chemicals [1]. Triphala is traditionally been used as laxative in chronic constipation, colon cleansing, digestion problems and poor food assimilation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Roxb, and Phyllanthus emblica Linn., is a widely prescribed traditional remedy that has been clinically used for thousands of years as treatment of various diseases and disorders. Numerous publications indicate that Triphala exerts potent antineoplastic activities against different types of cancer, including breast, colon, pancreas, prostate, ovarian, cervical, endometrial, and lymphatic cancer as well as melanoma [4, 5]. However, whether Triphala has similar effects on gastric cancer has not yet assessed in relevant reports.…”
Section: Introductionmentioning
confidence: 99%